The natural history of insomnia: a population-based 3-year longitudinal study. - Morin, C; Bélanger, L; LeBlanc, M; Ivers, H; Savard, J; Espie, C; Mérette, C; Baillargeon, L; Grégoire, J (2009)
BACKGROUND: Despite its high prevalence, little information is available about the natural history of insomnia. The extent to which episodes of insomnia will persist or remit over time is difficult to predict. We examined the natural history of insomnia and describe the most common trajectories over 3 years. METHODS: Three hundred eighty-eight adults (mean [SD] age, 44.8 [13.9] years; 61% women) were selected from a larger population-based sample on the basis of the presence of insomnia at baseline. They completed standardized sleep/insomnia questionnaires at 3 annual follow-up assessments. For each follow-up assessment, participants were classified into 1 of 3 groups (individuals with an insomnia syndrome, individuals with insomnia symptoms, and individuals with good sleep) on the basis of algorithms using standard diagnostic criteria for insomnia. Rates of persistent insomnia, remission, and relapse were computed for each group. RESULTS: Of the study sample, 74% reported insomnia for at least 1 year (2 consecutive assessments) and 46% reported insomnia persisting over the entire 3-year study. The course of insomnia was more likely to be persistent in those with more severe insomnia at baseline (ie, insomnia syndrome) and in women and older adults. Remission rate was 54%; however, 27% of those with remission of insomnia eventually experienced relapse. Individuals with subsyndromal insomnia at baseline were 3 times more likely to remit than worsen to syndrome status, although persistence was the most frequent course in that group as well. CONCLUSION: These findings indicate that insomnia is often a persistent condition, in particular when it reaches the diagnostic threshold for an insomnia disorder.